2019
DOI: 10.3390/electronics8121492
|View full text |Cite
|
Sign up to set email alerts
|

Deep, Consistent Behavioral Decision Making with Planning Features for Autonomous Vehicles

Abstract: Autonomous driving promises to be the main trend in the future intelligent transportation systems due to its potentiality for energy saving, and traffic and safety improvements. However, traditional autonomous vehicles’ behavioral decisions face consistency issues between behavioral decision and trajectory planning and shows a strong dependence on the human experience. In this paper, we present a planning-feature-based deep behavior decision method (PFBD) for autonomous driving in complex, dynamic traffic. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…These researches usually use microscopic simulations for the environment, such as Vissim [23], Udacity, [24], SUMO [25], or several self-made models [26]. Though hybrid solutions exist, where the strategic and direct control meets [27], only a few papers deal with defining a path by some geometric approach an RL and then drive through it with a controller [28], [29]. For further information on the topic, a good review of the RL based approaches for vehicle motion planning can be found in [30].…”
Section: A Related Workmentioning
confidence: 99%
“…These researches usually use microscopic simulations for the environment, such as Vissim [23], Udacity, [24], SUMO [25], or several self-made models [26]. Though hybrid solutions exist, where the strategic and direct control meets [27], only a few papers deal with defining a path by some geometric approach an RL and then drive through it with a controller [28], [29]. For further information on the topic, a good review of the RL based approaches for vehicle motion planning can be found in [30].…”
Section: A Related Workmentioning
confidence: 99%
“…Nevertheless, since there is a close coupling relationship between behavioral decision making and motion planning, in complex dynamic scenarios, there may be conflicts between the two layers. In a previous work [34], Qian et al proposed a decision-making algorithm using the planning feature in the training process for performance improvement. However, the planning feature used cannot completely represent the motion capability of the vehicles.…”
Section: Related Work and Research Background A Related Workmentioning
confidence: 99%
“…Two distinct coordination graph models, identity-based dynamic coordination and positionbased dynamic coordination, are studied in that work. Qian et al [123] described autonomous driving from a different perspective using twin delayed DDPG [155]. They proposed a two-level strategy to fill the gap between decision making and future planning of autonomous vehicle.…”
Section: A Autonomous Drivingmentioning
confidence: 99%